Strategies to Improve Mother's Own Milk Expression in Black and Hispanic Mothers of Premature Infants. (February 2022) - Cartagena, Diana; McGrath, Jacqueline M.; Reyna, Barbara; Parker, Leslie A.; McInnis, Joleen
Abstract : Background: Mother's own milk (MOM) is the gold standard of nutrition for premature infants. Yet, Hispanic and Black preterm infants are less likely than their White counterparts to receive MOM feedings. Evidence is lacking concerning potential modifiable factors and evidence-based strategies that predict provision of MOM among minority mothers of premature infants. Purpose: A review of the literature was conducted to answer the clinical question: "What evidence-based strategies encourage and improve mother's own milk expression in Black and Hispanic mothers of premature infants?" Methods/Search Strategy: Multiple databases including PubMed, Cochrane, and CINAHL were searched for articles published in the past 10 years (2010 through May 2020), reporting original research and available in English. Initial search yielded zero articles specifically addressing the impact of lactation interventions on MOM provision in minority mothers. Additional studies were included and reviewed if addressed breastfeeding facilitators and barriers (n = 3) and neonatal intensive care unit breastfeeding support practices (n = 7). Findings/Results: Current strategies used to encourage and improve MOM expression in minority mothers are based on or extrapolated from successful strategies developed and tested in predominantly White mothers. However, limited evidence suggests that variation in neonatal intensive care unit breastfeeding support practices may explain (in part) variation in disparities and supports further research in this area. Implications for Practice: Neonatal intensive care unit staff should consider implementing scaled up or bundled strategies showing promise in improving MOM milk expression among minorities while taking into consideration the cultural and racial norms influencing breastfeeding decisions and practice. Implications for Research: Experimental studies are needed to evaluate the effectiveness of targeted and culturally sensitive lactation support interventions in Hispanic and Black mothers.